The correlation between neonatal parameters and late‐onset inner ear disorders in congenital cytomegalovirus infection: a 10‐year population‐based cohort study. (28th September 2021) - Wu, Pei‐Hsuan; Lee, Chia‐Yi; Huang, Jing‐Yang; Yang, Shun‐Fa; Shih, Cheng‐Ping
Abstract: Objective: To evaluate the correlation of neonatal parameters with late‐onset sensorineural hearing loss (SNHL) and vestibular dysfunction in individuals with congenital cytomegalovirus (cCMV) infection using the National Health Insurance Research Database (NHIRD) in Taiwan. Design: Retrospective cohort study. Setting: The whole Taiwanese population. Participants: Patients with related diagnostic codes and examinations in their records were regarded as having cCMV infection. Each subject in that group was matched to 10 control individuals with noncongenital CMV infection on the basis of several neonatal parameters, including low gestational age, low birth weight, low Apgar score, maternal history of CMV infection and prolonged cCMV infection. A total of 5893 and 58 930 participants were enrolled in the study and control groups, respectively. Main outcome measures: The main outcomes were the development of SNHL and the development of vestibular dysfunction within one year after birth as reflected by diagnostic codes and specific examinations. Cox proportional hazard regression was used to calculate the adjusted hazard ratio (HR) and 95% confidence interval (CI) of each primary outcome between the two groups. Results: Overall, 109 and 397 episodes of SNHL developed in the study group and the control group, respectively, and the study group demonstrated a significantly higher incidence of SNHL (adjusted HR: 2.56; 95% CI: 2.07–3.18). In addition, similar incidence rates of vestibular dysfunction were found in the study group and the control group, with 7 and 90 events, respectively (adjusted HR: 0.77; 95% CI: 0.36–1.67). In subgroup analyses, a higher incidence of SNHL was correlated with lower gestational age (GA) (adjusted HR: 2.09; 95% CI: 1.29–3.39), lower birth weight (BW) (adjusted HR: 2.05; 95% CI: 1.28–3.30) and prolonged cCMV infection (adjusted HR: 3.92; 95% CI: 1.95–7.88). Conclusions: Low GA, low BW and a long disease course are significantly correlated with late‐onset SNHL in cCMV infection.